DEMONSTRATING FREE FALL - A TECHNICAL AND HISTORICAL INTERDISCIPLINARY APPROACH - KORYTAR, Jindrich; KROTKY, Jan; HONZIK, Lukas (Trends in education, 2016)
The article is devoted to the study of free fall from two points of view, the theoretical and the practical and experimental. By free fall is demonstrated the law of conservation of energy, especially with regard to teaching in primary, secondary and high schools. That is a key law, a base for all energy transformations and much more. Free fall may not be just a typically physical topic. There are many of the old or new inventions profiting from the physical law. One of them is a guillotine. Such a simple technical solution in the form of an executing tool allows you to implement not just a number of technological processes, but also large numbers of various physical measurements using school measuring systems.
Keywords: teaching aids; free fall; guillotine